Greenness and chronic respiratory health issues: a systematic review and meta-analysis - Tang, Mingcheng; Liu, Wei; Li, Haifang; Li, Fengyi (Frontiers in Public Health, 2023)
The number of chronic respiratory disease (CRD) individuals worldwide has been continuously increasing. Numerous studies have shown that greenness can improve chronic respiratory health through different mechanisms with inconsistent evidence. By quantitatively summarizing existing studies, our purpose is to determine the connection between greenness exposure and various chronic respiratory health. We conducted a comprehensive search on PubMed, EMBASE, and Web of Science core databases to identify relevant studies on the correlation between greenness exposure and chronic respiratory health. Studies published up to January 2023 were included in the search. The study used the most frequent indicator (normalized difference vegetation index [NDVI]) as the definition of greenness exposure. We finally identified 35 studies for meta-analysis. We calculated pooled effects across studies using a random-effects model and conducted a subgroup analysis by age and buffer zones to discuss the effects on chronic respiratory health. This study showed that 0.1 increments in NDVI were significantly related with lower rates of asthma incidence, lung cancer incidence, and chronic obstructive pulmonary disease (COPD) mortality risk, the pooled RRs were 0.92 (95%CI:0.85-0.98), 0.62 (95%CI:0.40-0.95) and 0.95 (95%CI:0.92-0.99), respectively. For age subgroup, the higher greenness exposure level was related to the incidence rate of asthma with teenagers aged 13-18y (RR 0.91 95%CI 0.83 0.99). For buffer subgroup, a positive relationship with greenness exposure and asthma incidence/prevalence at 200-300 m and 800-1000 m buffers, and the COPD mortality at 800-1000m buffer, the pooled RRs were 0.92 (95%:0.86-0.98), 0.87 (95%:0.81-0.93) and 0.93 (95%:0.88-0.98), respectively. Evidence of publication bias was not detected in this study. Our study is the first global meta-analysis between greenness and various CRDs which reported an inverse association. Further research is needed in order to determine the effect of greenness exposure on different CRDs. Therefore, when planning for green development, more consideration must be given to public health, as well as green management as an intervention measure aimed at improving public health.